Knowledge, Obstacles and Options for Implementing Active Learning: A Descriptive Cross-sectional Study from a Medical College in Central Nepal - Anwer Khan, Gulam; Shrestha, Amit; Timilsina, Sameer; Gautam, Ajeevan; Shakya, Shuvechha (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Education is a dynamic process that needs periodic refining. Lack of innovative teaching techniques in academics make medical education inadequate in making a significant stride towards the future. Didactic lectures (DL) have been the gold standard and the most common method of traditional teaching and learning practice. Active learning improves knowledge-sharing process facilitate development of analytical approaches to a problem solving and develops critical thinking. The aim of this study is to evaluate the knowledge, obstacles and options implementing active learning for among current teaching faculties of different affiliation. Methods: A descriptive, cross-sectional study was conducted on August 2022 among seventy-eight study participants. They were instructed to fill in the preformed proforma after obtaining written consent. Statistical analysis done using SPSS. Results: Fifty-two (66.7 percent) of participants strongly favored that active learning imparts better content knowledge, with forty-six (59 percent) of participants strongly agreeing that lack of insufficient student-teacher interaction is obstacle for active learning. Forty-four (56.4 percent) participants strongly agreed that group work facilitates active learning. Conclusion: Active learning methods can be implemented in the medical curriculum as medical educators are aware of the challenges and obstacles of this teaching learning method. It can develop lifelong learning skills among the students and teachers.